Oral health status among individuals with substance use disorder: Study cross sectional - Luthfiyah, Ananda Meidy; Theresia, Tiarma Talenta; Astoeti, Tri Erri; Louisa, Marie; Putri, Anzany Tania Dwi (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACTIntroduction: Drug abuse can lead to dependence and result in various health problems, particularly affecting oral health, including dental caries and periodontal disease. These oral health issues may further compromise the overall oral condition of individuals with Substance Use Disorder (SUD). This study aimed to determine the oral and dental health status of individuals with SUD at the Lido Rehabilitation Center of the National Narcotics Agency. Methods: This study was an observational descriptive study with a cross-sectional design, using a purposive (non-probability) sampling method. Data were collected through clinical examination using WHO caries index, converted into DMF-T, OHI-S, Gingival Index, Periodontal Pocket Depth, and tooth mobility among 101 respondents. Results: Of the 101 respondents, 98 (97%) presented with dental caries, while 3 (3%) were caries-free, with an average DMF-T score of 9.43. The majority of respondents demonstrated good oral hygiene (53%) and mild gingival inflammation (53%). Additionally, tooth mobility was rarely observed, and most respondents exhibited normal periodontal pocket depth. Specifically, 61 out of 101 respondents had normal periodontal pocket measurements. Conclusions: Individuals with SUD at the National Narcotics Agency Rehabilitation Center in Lido exhibit a high prevalence of dental caries, despite presenting with generally good oral hygiene, mild gingival inflammation, normal periodontal pocket depth, and minimal tooth mobility.KEY WORDS: individual with substance use disorder, caries, oral hygiene, periodontal disease.Status kesehatan gigi dan mulut pada penyalahguna narkoba : Studi cross sectionalABSTRAKPendahuluan: Penyalahgunaan narkoba dapat menyebabkan ketergantungan dan menimbulkan masalah kesehatan tubuh, terutama kesehatan gigi dan mulut seperti karies dan penyakit periodontal. Masalah kesehatan gigi dan mulut tersebut dapat mempengaruhi kesehatan gigi dan mulut terhadap pengguna narkoba. Tujuan penelitian mengetahui status kesehatan gigi dan mulut pada penyalahguna narkoba di Balai Besar Rehabilitasi Badan Narkotika Nasional Lido. Metode: Penelitian observasional deskriptif dengan rancangan cross-sectional dan metode purposive sampling (non - probability sampling). Pengambilan data dengan pemeriksaan klinis berupa indeks WHO yang diubah menjadi DMF-T, OHI-S, Gingival Index, kedalaman poket periodontal, dan kegoyangan gigi pada 101 responden. Hasil: Sebanyak 101 responden, 98 (97%) responden yang mengalami karies dan 3 (3%) responden tidak mengalami karies atau sehat dengan nilai rerata DMF-T 9,43. Sebagian besar responden memiliki kebersihan gigi dan mulut dalam kategori baik (53%) dan tingkat keparahan gingivitis kategori peradangan ringan (53%). Selain itu, hampir tidak ditemukan kegoyangan gigi pada seluruh responden dan sebagian besar gigi memiliki kedalaman poket periodontal normal. Kedalaman poket periodontal adalah normal pada 61 responden dari total 101 responden. Simpulan: Penyalahguna narkoba di Balai Besar Rehabilitasi Badan Narkotika Nasional Lido memiliki prevalensi karies yang tinggi walaupun tingkat kebersihan gigi dan mulut dalam kategori baik, tidak ada peradangan gingiva, tidak ada kedalaman poket periodontal, dan tidak ada kegoyangan gigi pada sebagian besar responden.KATA KUNCI: penyalahguna narkoba, kebersihan gigi dan mulut, karies, penyakit periodontal.